2021
DOI: 10.1039/d0sc05404f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide and hydrogen (syngas) as a C1-building block for selective catalytic methylation

Abstract: A broadly applicable catalytic process for the selective β-methylation of alcohols is presented using syngas (CO/H2) directly as a C1 building block and the shown manganese complex in the presence of a base as the catalytic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…In line with the catalytic activity of Mn-MACHO complexes for CO hydrogenation, [12,16] 3 shows a high tolerance towards the presence of CO (Table 2, Entry 7). Even with additional 5 bar of CO, a high yield of methanol was obtained.…”
supporting
confidence: 54%
“…In line with the catalytic activity of Mn-MACHO complexes for CO hydrogenation, [12,16] 3 shows a high tolerance towards the presence of CO (Table 2, Entry 7). Even with additional 5 bar of CO, a high yield of methanol was obtained.…”
supporting
confidence: 54%
“…Our group recently demonstrated that the formate ester pathway opens a possible entry into a CO hydrogenation manifold for catalytic methylation reactions using Syngas as a C1 source. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Previously, the groups of Marchionna, Ohyama, , and Mahajan , investigated the catalyst system Ni­(CO) 4 /base for the hydrogenation of CO in the presence of methanol, demonstrating that the resulting Ni species were operating as homogeneous catalysts. Our group recently demonstrated that the formate ester pathway opens a possible entry into a CO hydrogenation manifold for catalytic methylation reactions using Syngas as a C1 source …”
Section: Resultsmentioning
confidence: 99%
“…Hence, the direct use of syngas as a C1‐building block for C‐methylation reactions is also interesting. In this regard, recently, Leitner and co‐workers [26] reported the application of syngas (CO+H 2 ) for β ‐methylation of alcohols in the presence of [Mn( i Pr‐MACHO)(CO) 2 Br] complex Mn‐catalyst ( 2 ). Under the optimized reaction conditions (2 mol% Mn‐catalyst ( 2 ), 2 equiv.…”
Section: Manganese‐catalyzed C‐methylation Reactions Using Methanolmentioning
confidence: 99%
“…The presence of the alcohol substrate is essential to facilitate the hydrogenation of carbon monoxide via formate ester as intermediate(Scheme 17). [26] …”
Section: Manganese‐catalyzed C‐methylation Reactions Using Methanolmentioning
confidence: 99%